2015
DOI: 10.1039/c5sc00832h
|View full text |Cite
|
Sign up to set email alerts
|

What causes extended layering of ionic liquids on the mica surface?

Abstract: The adsorbed water on the mica surface is the key to the extended layering of ILs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 65 publications
(119 citation statements)
references
References 41 publications
(64 reference statements)
8
110
1
Order By: Relevance
“…As the adsorbed water molecules were released due to heating, hydrocarbon contaminants might replace the water molecules on the mica surface . The adsorbed contaminants would likely block the interaction between K ions and negative vacancies in the frame of mica . This should lead to the decrease in adhesion energy of the MNL mica system.…”
Section: Resultsmentioning
confidence: 99%
“…As the adsorbed water molecules were released due to heating, hydrocarbon contaminants might replace the water molecules on the mica surface . The adsorbed contaminants would likely block the interaction between K ions and negative vacancies in the frame of mica . This should lead to the decrease in adhesion energy of the MNL mica system.…”
Section: Resultsmentioning
confidence: 99%
“…Since most of the above‐mentioned solid surfaces, for example, silica and mica, are believed to be negatively charged, it is generally accepted that the electrostatic interactions at IL/solid interface is critical to the extended layering of RTILs . Recent research in our lab demonstrated that, adsorbed water is the key reason to the extended layering of ILs on the mica surface . The AFM results (Figure ) clearly revealed that ILs form extended layering when water is adsorbed on the mica surface under ambient conditions, while droplet structure, that is, dewetting, occurs on the mica surface, when the water is removed by heating at elevated temperatures.…”
Section: Ionic Liquids: Liquids or Solids?mentioning
confidence: 86%
“…(right) Corresponding line profiles. Reproduced with permission . Copyright 2015, The Royal Society of Chemistry.…”
Section: Ionic Liquids: Liquids or Solids?mentioning
confidence: 99%
“…[10] For example, Liu et al [11] reported a novel method to fabricate a robust and corrosion resistant superhydrophobic aluminum alloy surface which has good mechanical stability. [17,18] This cleaner emits a high-intensity UV light with both 185 and 254 nm wavelengths. [12][13][14] However, the synthesis of nanoparticles is usually complex and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…UV/ozone treatment was conducted on some alumina/glass samples, using a BioForce Nanosciences UV/ozone ProCleaner. [17,18] This cleaner emits a high-intensity UV light with both 185 and 254 nm wavelengths. The UV/ozone treatment was conducted in the ambient air and for a time period of 10 min for all the samples treated.…”
Section: Introductionmentioning
confidence: 99%